SISTEM LABORATORIUM BAHASA DI DALAM WHATSAPP MESSENGER - Irma Nurul Husnal Chotimah (Universitas Hasanuddin, 2020)
By the research and development (R&D) method designed by Nicolas Guichon (2007)), this scientific paper lists and describes the features of the free WhatsApp Messenger apps version 2.20.193.9 (released by WhatsApp Inc.) which is then analyzed using the theory of a language laboratory system made by Alfred S. Hayes for later analysis results are used to develop a virtual language laboratory manual. The purpose of this paper is to find out the features of the Whatsapp Messenger version 2.20.193.9 application that can be used for virtual language laboratories and also to develop its manual. Based on the results of the analysis that the author has done, the features that can be used for virtual language laboratories are the chat group, message, voice message, voice call, voice-video call, document delivery (voice document, video, text). The results of this study will be used for the development of the virtual language laboratories manual and are also expected to a topic of discussion among researchers and practitioners in the field of foreign language education and teaching.